Evolution of core network oriented to 5G - Hongyuan MA; Ziyu XIAO; Zhonggui BU; ·uan ZHAO (Dianxin kexue)
The 5G network is dedicated to the vision of “internet of everythingand information is easy to reach”.5G network adopts scene design to meet diverse business needs in a more flexible way.Based on the core network target architecture oriented to 5G,the problems in network evolution were analyzed from the aspects of network equipment form,networking architecture,network and service capabilities,and network management orchestration.Following the principle of “one-step network architecture layout,smooth evolution of network element functions,and gradual migration adjustment of capacity traffic”,the 5G evolution strategy recommendations for different periods were given.